Activity of nanoemulsion botanical insecticides from Myristica fragrans and Jatropha curcas essential oil against Sitophilus zeamais - NI SILUH PUTU NURYANTI; LINA BUDIARTI; DULBARI DULBARI; HERY SUTRISNO; DENNY SUDRAJAT; YURIANSYAH YURIANSYAH; PRIYADI PRIYADI; RIZKY RAHMADI; FAJAR ROCHMAN; EVI YUNITA SARI; JUWITA SURI MAHARANI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Nuryanti NSP, Budiarti L, Dulbari, Sutrisno H, Sudrajat D, Yuriansyah, Priyadi, Rahmadi R, Rochman F, Sari EY, Maharani JS. 2023. Activity of nanoemulsion botanical insecticides from Myristica fragrans and Jatropha curcas essential oil against Sitophilus zeamais. Biodiversitas 24: 5610-5617. Maize weevils also known as Sitophilus zeamais, are primary pests that decrease in the quality and quantity of grain products. This study aimed to examine the impact of nanoemulsion formulas of Myristica fragrans and Jatropha curcas essential oils on S. zeamais adults. The investigation focused on the toxicity, ability to inhibit population growth, intensity of damage caused, and effect on seed weight loss. The essential oils were extracted using the distillation method, and the toxicity was tested through contact, fumigant, and seed dressing. A probit program was used to analyze the toxicity level (LC50 and LC95). The results showed that M. fragrans essential oil had the highest toxicity in contact treatment and the lowest when applied via fumigation. Furthermore, this method shows an LC50 value for the contact method of 0.53% and fumigation of 1.01%, while the LC95 value is 4.38% and 10.60% respectively. Based on the LC95 botanical insecticide from J. curcas, all three methods were toxic to S. zeamais adults, with contact being the highest, followed by seed dressing, and fumigant, at 5.23, 6.44, and 19.94%, respectively. The botanical insecticides derived from M. fragrans essential oil through contact provided the best inhibitory activity on population development, intensity of damage, and seed weight loss, with values of 18.00, 16.81, and 13.96%. Plant-based pesticides not only cause pest mortality but also maintain seed quality by reducing weight loss, intensity of pest attacks, and inhibiting the development of pest populations in storage.